2019
DOI: 10.1111/jfb.14003
|View full text |Cite
|
Sign up to set email alerts
|

Enormous gill chambers of deep‐sea coffinfishes (Lophiiformes: Chaunacidae) support unique ventilatory specialisations such as breath holding and extreme inflation

Abstract: Deep sea habitats tend to favor species with low energetic demands, and therefore we predict that deep sea fishes will have behavioral and morphological specializations of the gill ventilatory system to reduce the energetic cost of pumping water across the gills. However, it is difficult to study functional morphology of deep sea fishes due the lack of ability to conduct laboratory experiments with living fishes. For this study, we combined analysis of publicly available video recorded by remote‐operated vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…comm., 18 December 2021). Long and Farina (2019) reported gill chamber (i.e., not the stomach) inflation in chaunacids during ventilation and suggested that such inflation may play a defensive role because it increases body size. Inflation may occur in frogfishes (Antennariidae; see Pietsch and Arnold, 2020: 452–454; also Ferreira et al, 2022), but the evidence and mechanism are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…comm., 18 December 2021). Long and Farina (2019) reported gill chamber (i.e., not the stomach) inflation in chaunacids during ventilation and suggested that such inflation may play a defensive role because it increases body size. Inflation may occur in frogfishes (Antennariidae; see Pietsch and Arnold, 2020: 452–454; also Ferreira et al, 2022), but the evidence and mechanism are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is hard to calculate the area of opercular directly using machine vision. However, alternative characteristics can be measured, such as the time of each phase of ventilation (Zheng et al 2014;Farina & Bemis 2016;Long & Farina 2019). Conversely, ventilation activity has apparent external and internal changes.…”
Section: Ventilation Frequencymentioning
confidence: 99%
“…Body inflation is an antipredator defensive mechanism [1]. Examples among vertebrates include amphibians and reptiles that use lung or buccal cavity inflation [2,3], the coffinfishes (Chaunacidae) that inflate by storing a substantial volume of water in their gill chambers [4], and notably within the stomach inflating pufferfishes and porcupine fishes (Tetraodontidae and Diodontidae sister families, respectively, Tetraodontiformes), herein referred to as 'pufferfishes', for simplicity. Pufferfishes can increase up to three times their body size by swallowing large amounts of water that is held within the stomach [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Pepsinogens are fundamental for acid-peptic digestion where the conversion from pepsinogen to pepsin (the active form) is promoted by both HCl and auto-catalysis [23,24]. In this way, gastric acidity promotes protein digestion and cell lysis, facilitating the release and absorption of nutrients [25], improving PO 4 3− and Ca 2+ uptake, and providing innate immune protection against pathogen entry into the intestine [19,22,26]. Surprisingly, despite the major advantages of a functional acid-peptic stomach, several secondary loss events of structure and function have occurred in the gnathostome lineage, most commonly in the Teleostei, but also in the Holocephali, dipnoids and monotremes [21, [27][28][29].…”
Section: Introductionmentioning
confidence: 99%